Competencia y jurisdicción de los notarios para escrituras electrónicas en Babahoyo - Ramirez Silva, Erika Gabriela (2025)
The analysis of the digital transformation of notarial services in Ecuador showed that the telematic notarial service emerged as a solution to the contemporary needs of efficiency and access to justice. The general objective of this research was to analyze the impact of the telematic notarial service on the competence and jurisdiction of notaries in Babahoyo canton for the execution of electronic deeds. For this purpose, a qualitative methodological approach was used, applied through interviews with notaries, administrative staff and users, as well as the analysis of regulatory documents and relevant resolutions. The results revealed that, although digitalization has improved operational aspects, the lack of adequate technological infrastructure and the lack of training to clarify the functionalities of the system continue to be obstacles. In addition, regulatory gaps were identified that impede the optimal functioning of the telematic service, questioning its security and authenticity in the digital context. It was concluded that it is urgent to make regulatory and operational adjustments to consolidate citizen confidence in digital notaries, optimize processes and ensure respect for the principles of Ecuadorian notarial law. Finally, it was recommended to undertake actions that include updating regulations, training personnel and strengthening the technological infrastructure as fundamental pillars for the success of the modernization of the notarial service in Ecuador.